Rivaroxaban Compared to Placebo for the Treatment of Leg Superficial Vein Thrombosis: A Randomized Trial - Kearon, Clive; Carrier, Marc; Gu, Chu-Shu; Schulman, Sam; Bates, Shannon M.; Kahn, Susan R.; Chagnon, Isabelle; Nguyen, Doan Trang; Wu, Cynthia; Rudd-Scott, Lisa; Julian, Jim A. (Seminars in Thrombosis and Hemostasis, 2020)
The role of rivaroxaban in the treatment of leg superficial venous thrombosis (SVT) is uncertain. This article aims to determine if rivaroxaban is an effective and safe treatment for leg SVT. Patients with symptomatic leg SVT of at least 5 cm length were randomized to 45 days of rivaroxaban 10 mg daily or to placebo, and followed for a total of 90 days. Treatment failure (required a nonstudy anticoagulant; had proximal deep vein thrombosis or pulmonary embolism; or had surgery for SVT) at 90 days was the primary efficacy outcome. Secondary efficacy outcomes included leg pain severity, and venous disease-specific and general health-related quality of life over 90 days. Major bleeding at 90 days was the primary safety outcome. Poor enrollment led to the trial being stopped after 85 of the planned 600 patients were randomized to rivaroxaban (n = 43) or placebo (n = 42). One rivaroxaban and five placebo patients had a treatment failure by 90 days (absolute risk reduction = 9.0%, 95% confidence interval: −22 to 5.9%). Leg pain improvement did not differ at 7 (p = 0.16) or 45 days (p = 0.89), but was greater with rivaroxaban at 90 days (p = 0.011). There was no difference in venous disease-specific (p = 0.99) or general health-related (p = 0.37) quality of life over 45 days. There were no major bleeds or deaths in either group. There were no identifiable differences in efficacy or safety between rivaroxaban and placebo in patients with symptomatic SVT but comparisons were undermined by a much smaller than planned sample size (NCT1499953).
Keywords: superficial vein; clinical trial; treatment; leg; venous thrombosis